Recent Advances in Systemic Treatments for HER-2 Positive Advanced Gastric Cancer - Kahraman, Seda (Onco Targets Ther, 2021)
Gastric cancer (GC) is the fifth most common cancer worldwide. Despite recent improvements in treatment quality and options, advanced gastric cancer remains one of the hardest to cure cancers, with a median overall survival (OS) of 10–12 months and a 5-year OS of approximately 5–20%. There is an unmet need for further efforts to palliate disease-related symptoms, improve quality of life, increase tumor response rate, and prolong progression free and overall survival while balancing the toxicities of therapy. The most common type of GC is adenocarcinoma, which demonstrates morphological, biological, and clinical heterogeneity. A plethora of genomic alterations and the activation of numerous molecular pathways including human epidermal growth receptor 2 (HER2), epidermal growth factor receptor (EGFR), fibroblast growth factor receptor-2 (FGFR2), mesenchymal epidermal transforming factor receptor (MET), and the phosphatidylinositol 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) are responsible for the complex heterogeneity of GC. Efforts to validate the therapeutic effects of inhibiting some of these aberrantly expressed pathways have failed to lead to a clinically meaningful outcome apart from the overexpression/amplification of the HER2 gene, inhibition of which has had a significant impact on clinical practice. The only available biomarkers to guide the effective treatment of patients with advanced GC are HER2 overexpression, MSI/PD-L1 status, and FGFR alterations. Various anti-HER2 agents have been evaluated after the success of the ToGA trial, but none led to a significant enough clinical improvement to be considered a viable alternative for HER2-targeted therapy in advanced GC until the global Keynote-811 trial, which added pembrolizumab to trastuzumab in combination with chemotherapy. This combination demonstrated a survival advantage for the first time in the 11 years since ToGA. Trastuzumab deruxtecan (T-DXd) was also found to be effective in patients who had already received >2 previous lines of treatment. Despite these promising avenues, the optimal management of HER-2 positive GC still requires further development.